Nodulation and estimation of symbiotic nitrogen fixation by herbaceous and shrub legumes in Guinea Savanna in Nigeria - Sanginga, N.; Wirkom, L.E.; Okogun, A.; Akobundu, I.O.; Carsky, R.J.; Tian, G. (Springer, 1996)
Twelve herbaceous and shrub legume species were grown in pot and field experiments in five sites representing three agroecological zones in moist savanna in Nigeria. The objectives were to: (1) assess natural nodulation of the legumes and characterize their indigenous rhizobia, (2) determine their need for rhizobia inoculation and (3) estimate the amount of N2 fixed by each of these legumes. At 4 weeks after planting (WAP), Crotolaria verrucosa was not nodulated at any of the sites while Centrosema pascuorum had the highest number of nodules in all sites. At 8 WAP, all legumes were nodulated, with Mucuna pruriens having the least number of nodules and Stylosanthes hamata the highest. The number of nodules, however, was inversely correlated to the mass of nodules. Significant differences in nodulation of the legume species grown in the field also occurred between and within sites. Mucuna pruriens and Lablab purpureus produced more shoot and nodule biomass than the other legumes in all sites. Growth of most of these legumes responded to fertilizer application, except for C. verrucosa and Aeschynomene histrix. Except for C. verrucosa, average proportion of N2 fixed was about 80% and this was reduced by about 20% with N fertilizer application. The majority of rhizobia isolates (60%) were slow growing, belonging to the Bradyrhizobia spp. group. Selected rhizobia isolates evaluated on Cajanus cajan, C. pascuorum, M. pruriens and Psophocarpus palustris varied from ineffective to highly effective in Leonard jar conditions. However, only growth of M. pruriens responded to inoculation in potted soils, whereas it was lower than that obtained with N fertilizer application. This indicated the need to screen more rhizobia in order to improve N2 fixation and growth of legume species such as M. pruriens when it is introduced in soils deficient in N.